Precocious Phenotypic Transcription‐Factor Expression During Early Development. Issue 5 (11th January 2017) - VanOudenhove, Jennifer J.; Medina, Ricardo; Ghule, Prachi N.; Lian, Jane B.; Stein, Janet L.; Zaidi, Sayyed K.; Stein, Gary S.
ABSTRACT: A novel role for phenotypic transcription factors in very early differentiation was recently observed and merits further study to elucidate what role this precocious expression may have in development. The RUNX1 transcription factor exhibits selective and transient upregulation during early mesenchymal differentiation. In contrast to phenotype‐associated transcriptional control of gene expression to establish and sustain hematopoietic/myeloid lineage identity, precocious expression of RUNX1 is functionally linked to control of an epithelial to mesenchymal transition that is obligatory for development. This early RUNX1 expression spike provides a paradigm for precocious expression of a phenotypic transcription factor that invites detailed mechanistic study to fully understand its biological importance. J. Cell. Biochem. 118: 953–958, 2017. © 2016 Wiley Periodicals, Inc. Abstract : A novel role for phenotypic transcription factors in very early differentiation was recently observed and merits further study to elucidate what role this precocious expression may have in development. The RUNX1 transcription factor exhibits selective and transient upregulation during early mesenchymal differentiation.